Pemilihan Metode Perbaikan Struktur Condensate Jetty: Systematic Literature Review - Andri Sastrawan (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of oil and gas industry infrastructure has increased the demand for specialized port facilities such as jetties that function as key infrastructure for the distribution of energy products through maritime transportation. Jetty structures operating in marine environments are exposed to various aggressive environmental factors including high humidity, corrosion, and climatological conditions that can accelerate material degradation and reduce structural performance. This study aims to analyze previous research findings related to structural deterioration and repair approaches in order to provide a comprehensive understanding of jetty repair strategies. The research employs a Systematic Literature Review approach using the PRISMA guideline to identify, screen, and synthesize relevant scientific articles. The literature selection process resulted in 16 articles that met the inclusion criteria and were analyzed qualitatively. The results indicate that environmental factors such as moisture intrusion, water penetration, climatological conditions, and microbiologically induced corrosion significantly influence structural deterioration. In addition, several studies highlight the importance of damage identification, reliability analysis, and understanding material deterioration characteristics in determining appropriate repair strategies. The discussion suggests that selecting appropriate repair methods requires consideration of environmental conditions, types of structural damage, and available repair technologies. In conclusion, this literature review provides a comprehensive understanding of deterioration factors and repair approaches for jetty structures that can serve as a reference for future research and engineering practice in marine infrastructure.